2020
DOI: 10.1016/j.hpb.2020.04.802
|View full text |Cite
|
Sign up to set email alerts
|

Patients with deleterious germline mutations: a heterogeneous population for pancreatic cancer screening?

Abstract: Background: Many germline mutations are associated with an increased risk of pancreatic adenocarcinoma (PDAC). Screening at our institution is currently offered for mutation carriers or patients with at least one first-degree relative or two family members with PDAC. High-risk screening protocol includes complete history and physical examination, tumor markers (CA19-9 and CEA), and crosssectional imaging (CT or MRI/MRCP with Gadolinium and Secretin enhancement), followed by semi-annual to annual clinic visits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Germline variants in PC susceptibility genes in individuals with IPMN include STK11 , MSH2 , MSH6 , PMS2 , BRCA2 , BRCA1 , ATM , CDKN2A , PALB2 , and APC. 20,24–30 Next-generation sequencing analysis of the proband revealed a germline MSH6 missense variant (p.Tyr1066Cys), suggesting its potential role as a susceptibility variant for both IPMN and PC. Because of the highly conserved nature of this tyrosine residue and the large physicochemical differences between tyrosine and cysteine, MSH6 missense variant (p.Tyr1066Cys) is often identified as pathogenic by various in silico pathogenicity prediction tools.…”
Section: Discussionmentioning
confidence: 99%
“…Germline variants in PC susceptibility genes in individuals with IPMN include STK11 , MSH2 , MSH6 , PMS2 , BRCA2 , BRCA1 , ATM , CDKN2A , PALB2 , and APC. 20,24–30 Next-generation sequencing analysis of the proband revealed a germline MSH6 missense variant (p.Tyr1066Cys), suggesting its potential role as a susceptibility variant for both IPMN and PC. Because of the highly conserved nature of this tyrosine residue and the large physicochemical differences between tyrosine and cysteine, MSH6 missense variant (p.Tyr1066Cys) is often identified as pathogenic by various in silico pathogenicity prediction tools.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have analyzed mutations in IPMNs and extrapancreatic malignancy among patients with hereditary syndromes and have reported similar genetic alterations ( Table 5 ). A multivariate analysis revealed that germline mutations among patients with hereditary cancer syndromes was a predictor of the presence of IPMNs (relative risk, 3.2; 95% confidence interval (CI): 1.6–6.4) independent of family history of pancreatic cancer ( p = 0.22) [ 80 ]. These data suggest that hereditary syndromes may predispose patients to IPMNs, which, in turn, increases the risk of PDAC formation.…”
Section: Ipmns In Hereditary Genetic Predisposition Syndromesmentioning
confidence: 99%